Research of Force Dependences at Diamond Ironing - Saidova Mukhabbat Hamroevna; Juraev Jurabek Malikovich; Zainiev Khudoyberdi Mukhiddinovich (Research Parks Publishers, 2021)
The article covers the force dependences at diamond ironing at the beginning of movement with various mandrels, in contrast to the mandrel with a rigid structure: a pneumatic mandrel and a pneumatic mandrel on springs.